An automatic VHF transmitter monitoring system for wildlife research - A. Torbjörn Johansson; Örjan Johansson; Tom McCarthy (Wildlife Society Bulletin)
Abstract We describe an automated system for monitoring multiple very high frequency (VHF) transmitters, which are commonly employed in wildlife studies. The system consists of a microprocessor‐controlled radio‐frequency monitor equipped with advanced signal‐processing capabilities that communicates with, and relays information to, a user interface unit at a different location. The system was designed for a capture‐and‐release snow leopard (Panthera uncia) study in Mongolia, where checking trap‐site transmitters manually entailed climbing a hill with telemetry equipment several times each day and night. Here, it monitors the trap‐site transmitters and actively produces an alarm when any of the traps have been triggered, or if the system has lost contact with any trap‐transmitter. The automated system allowed us to constantly monitor transmitters from a research camp, and alerted us each time a trap was triggered. The system has been field‐tested for 83 days from mid‐September 2010 to mid‐December 2010 in the Tost mountain range on the edge of Mongolia's Gobi desert. During this time, the system performed reliably, responding correctly to 45 manually generated alarms and 9 animal captures. The system considerably shortens the time the captured animals spend in traps, and also mitigates the need for manual trap‐site transmitter monitoring, greatly reducing risk to the animal and the human effort involved. © 2011 The Wildlife Society.